POSSE (Predict, Organize, Search, Summarize, and Evaluate) Strategy Towards Reading Comprehension Achievement - Agung Setiadi (Channing : Journal of English Language Education and Literature, 2019)
This research aimed at finding out whether or not Predict, Organize, Search, Summarize, and Evaluate (POSSE) Strategy influence the students’ reading comprehension achievement of the eighth-grade students of SMP Muhammadiyah 2 Karang Tengah. The population consists of 99 students. The sample was 69 students taken through purposive sampling. In this research, the researcher used multiple-choice as an instrument for collecting the data. The data obtained from Independent t-test analysis, between the result of the posttest in the experimental group and the control group. Based on the calculation by using an Independent t-test, the researcher found that t-Obt. was higher than the t-table (4,115 > 2,000) and less than at the significant level α = 0.05(0.000 < 0.05) in a two-tailed test. So, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that the POSSE Strategy influence to teach reading comprehension achievement.